Pengaruh penambahan karet siklo terhadap sifat vulkanisat kompon karpet karet - Nurhajati, Dwi Wahini; Alfa, Ary Achyar (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2007)
Effect of cyclis rubber on the vulcanizate properties of fubber carpet compound was investigated. Carpet compounds were prepared by ribbed smoked sheets I (RSS I) and styrene butadiene rubber (SBR) as a raw material, and cyclis rubber in various amount was added as additive. The amounts of the added cyclis rubber were varied from 10 to 40 phr with range of 10 phr. The rubber carpet compound was produced by using a two roll-mills (Shanghai RMW, model XK-160, capacity 2 kg). The culcanizate properties of rubber carpet compound were tested base on SNI. 12-1000-1989 for karpet karet, and ASTM F.1859-2000 for rubber sheet floor covering without backing The results showed that cyclis rubber in the compound was focused as a filler. Generally, the physical properties of vulcanizates containing cyclis rubber was better than the vulcanizates without cyclis rubber. Effects of cyclis rubber on the vulcanize properties of rubber carpet compound have increase hardness, tensile strength elongation at break, dimensional stability, and slip resistance. The compound with ratio of cyclis rubber 10 phr performed the best physical properties i.e: 85 Shore A hardness, 1479.9 N/cm2 tensile strength, 372.44% elongation at break, 1.24 g/cm3 density, 433.33 N/cm2 compression resistance, 2.29 mm3/kg.m Graselli abrasion resistance, and 1.24 U coefficient slipping resistance on dry surface, respectively. Â Keywords: cyclis rubber, rubber carpet compound.Â ABSTRAKÂ Telah dilakukan penelitian mengenai pengaruh karet siklo yang merupakan produk modifikasi karet alam terhadap sifat vulkanisat kompon karpet karet. Kompon karpet karet dibuat dengan bahan baku karet asap lembaran (RSS) dan karet sintetis styrene butadiene (SRB), dan karet siklo sebagai aditif. Karet siklo yang ditambahkan jumlahnya divariasi dari 10 â 40 phr dengan kisaran kenaikan 10 phr. Pembuatan kompon karpet menggunakan alat two rolls-mills (Shanghai RMW, model XK-160, kapasitas 2 kg). Sifat fisis kompon karpet karet diuji berdasar SNI.12-1000-1989 untuk karpet karet maupun ASTM F.1859-2000 untuk rubber sheet floor covering without backing. Hasil penelitian menunjukkan bahwa karet siklo pada pembuatan karpet karet berfungsi sebagai bahan pengisi. Secara umum sifat fisis vulkanisat yang berisi karet siklo lebih baik daripada vulkanisat tanpa karet siklo. Karet siklo terbukti meningkatkan kekerasan, tegangan putus, perpanjangan putus, 372,44%, kerapatan massa 1,24 gr/cm3, ketahanan pampat 433,22 N/cm2, ketahanan kikis (Grasselli) 2,29 mm3/kg. m, dan ketahanan slip pada permukaan kering 1,24 koefisien U.Â Kata kunci: karet siklo, kompon karpet karet.